Analysis of Factors Affecting Accessibility of Health Services Regarding HIV/AIDS - Dimas Agung Nugroho; Edi Purwanto (Indonesian Journal of Global Health Research, 2026)
HIV/AIDS remains a global health problem that requires special attention regarding the accessibility of health services. Limited access due to several factors impacts the quality of life of people with HIV/AIDS (ODHA). Objective: To analyze the factors that influence the accessibility of health services for HIV/AIDS. Method: This study employed a cross-sectional design using data from the 2017 Indonesian Demographic and Health Survey, involving 2,944 respondents, with data analysis conducted through bivariate chi-square tests and multivariate logistic regression. The independent variables in this study were residence, gender, sources of HIV knowledge from health workers, health insurance status, and access to HIV testing facilities. Results: The results of this study indicate that factors that influence the accessibility of health services for HIV/AIDS, including residence (OR = 1.011; 95% Cl = 0.806-1.268), sources of knowledge from health workers (OR = 1.008; 95% Cl = 0.851-1.194), health insurance status (OR = 0.776; 95% Cl = 0.663-0.907), are more risky than other factors. The conclusion of this study is that community accessibility to health services related to HIV/AIDS is still limited, there are several factors that influence this condition. Conclusion: The most dominant factors related to inaccurate access to health services for HIV/AIDS are the variables of gender, residence, and sources of HIV knowledge from health workers. Meanwhile, the variable of health insurance access status has a significant relationship.